The Incentive Bias: Subject Underreporting of Adverse Drug Effects - Breton, Matthew (The Meducator, 2016)
I discuss my experience participating in a clinical trial and my encounters with other subjects. Through this unique position I gained the perspective of the typical study participant, which led to the discovery of fears which deter subjects from reporting symptoms. This incentive bias is caused by the financial duress of many participants, resulting in a high incentive to complete the study. Changes in health go unreported reported which skews adverse drug reaction data and leads to additional costs imposed to healthcare. Clinical trials should strive to eliminate incentive bias to improve the transparency and increase reporting fidelity.